2022
DOI: 10.3390/v14071417
|View full text |Cite
|
Sign up to set email alerts
|

Was the Reduction in Seasonal Influenza Transmission during 2020 Attributable to Non-Pharmaceutical Interventions to Contain Coronavirus Disease 2019 (COVID-19) in Japan?

Abstract: We quantified the effects of adherence to various non-pharmaceutical interventions (NPIs) on the seasonal influenza epidemic dynamics in Japan during 2020. The total monthly number of seasonal influenza cases per sentinel site (seasonal influenza activity) reported to the National Epidemiological Surveillance of Infectious Diseases and alternative NPI indicators (retail sales of hand hygiene products and number of airline passenger arrivals) from 2014–2020 were collected. The average number of monthly seasonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 80 publications
1
11
0
Order By: Relevance
“…Additionally, the number of patients with viral infections has significantly decreased due to strict infectious disease control measures implemented during the COVID-19 pandemic in Japan. [27][28][29] The results of our study, showing a decrease in the monthly number of patients with KD immediately after the COVID-19 pandemic started, are consistent with reports from local regions and a nationwide survey of KD between 2019 and 2020 in Japan. [16][17][18] To investigate the factors contributing to the decline in the number of patients with KD, we analyzed the trends in various viral infections in Japan from January 2018 to March 2022, assuming that KD is induced by viral infection.…”
Section: Resultssupporting
confidence: 90%
“…Additionally, the number of patients with viral infections has significantly decreased due to strict infectious disease control measures implemented during the COVID-19 pandemic in Japan. [27][28][29] The results of our study, showing a decrease in the monthly number of patients with KD immediately after the COVID-19 pandemic started, are consistent with reports from local regions and a nationwide survey of KD between 2019 and 2020 in Japan. [16][17][18] To investigate the factors contributing to the decline in the number of patients with KD, we analyzed the trends in various viral infections in Japan from January 2018 to March 2022, assuming that KD is induced by viral infection.…”
Section: Resultssupporting
confidence: 90%
“…Our findings correlate with the global influenza circulation attributable to the similar COVID-19 control measures were introduced across the globe, thus also affecting influenza transmission ( 6 , 7 ). A Japanese study reported that the adherence to NPIs such as strict adherence to proper hand hygiene practices as well as international travel restrictions was associated with decreased influenza activity ( 8 ). A modeling study in Ghana showed that introduction and adherence of NPIs (such as use of face masks, hand washing, closure of international and land borders) as well as reduced mobility negatively impacted COVID-19 transmission in the early phase of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…To establish a robust and reliable time-series statistical model, multiple stages were incorporated into it [ 11 , 53 , 54 ]. Prior to constructing the model, we checked the probability distribution of the dependent variables and number of weekly newly confirmed HRSV infection cases (the normality of probability distribution was assessed by the Shapiro–Wilk test) ( Figure S2 ), followed by an assessment of the relationships (e.g., linearity) between number of weekly newly confirmed HRSV infection cases and each independent variable.…”
Section: Methodsmentioning
confidence: 99%